Implementasi Model Project Based Learning dalam Meningkatkan Kreativitas Siswa di SMP Negeri 2 Tambusai - Harahap, Mariah; Panjaitan, Juni Herawati; Yasin, Karlina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The implementation of the Project-Based Learning (PjBL) model in this study has been proven to enhance students' creativity at SMP Negeri 2 Tambusai. Through a classroom action research (CAR) method with two cycles, this study observed students' progress in critical thinking, problem-solving, and the ability to generate innovative ideas. In the first cycle, students began to show increased participation in project activities, although challenges in time management and collaboration remained. The second cycle demonstrated more significant improvements, where students became more engaged in conceptualizing ideas, developing products, and presenting their projects. Questionnaire results revealed that most students were more motivated in project-based learning compared to conventional methods. However, the implementation of PjBL still faced challenges, such as limited facilities and the need for intensive teacher guidance. Therefore, school support in providing adequate infrastructure and enhancing teachers' skills is essential to optimize project-based learning outcomes.